"Memory Lane"- Recollections on the early years with Juan Mateu. Heartfelt Congratulations to our dear friend, Profesor Juan Mateu Bellés - Elisabeth K. Butzer (Cuadernos de Geografía de la Universitat de València)
Heartfelt Congratulations to our dear friend, Profesor Juan Mateu Bellés